Socioecological factors influencing women's HIV risk in the United States: qualitative findings from the women's HIV SeroIncidence study (HPTN 064). (December 2016) - Frew, Paula; Parker, Kimberly; Vo, Linda; Haley, Danielle; O'Leary, Ann; Diallo, Dazon; Golin, Carol; Kuo, Irene; Soto-Torres, Lydia; Wang, Jing; Adimora, Adaora; Randall, Laura; et al.
Abstract Background We sought to understand the multilevel syndemic factors that are concurrently contributing to the HIV epidemic among women living in the US. We specifically examined community, network, dyadic, and individual factors to explain HIV vulnerability within a socioecological framework. Methods We gathered qualitative data (120 interviews and 31 focus groups) from a subset of women ages 18–44 years (N  = 2, 099) enrolled in the HPTN 064 HIV seroincidence estimation study across 10 US communities. We analyzed data from 4 diverse locations: Atlanta, New York City (the Bronx), Raleigh, and Washington, DC. Data were thematically coded using grounded theory methodology. Intercoder reliability was assessed to evaluate consistency of team-based coding practices. Results The following themes were identified at 4 levels including 1) exosystem (community): poverty prevalence, discrimination, gender imbalances, community violence, and housing challenges; 2) mesosystem (network): organizational social support and sexual concurrency; 3) microsystem (dyadic): sex exchange, interpersonal social support, intimate partner violence; and 4) individual: HIV/STI awareness, risk taking, and substance use. A strong theme emerged with over 80 % of responses linked to the fundamental role of financial insecurity underlying risk-taking behavioral pathways. Conclusions Multilevel syndemic factors contribute to women's vulnerability to HIV in the US. Financial insecurity is a predominant theme, suggesting the need for tailored programming for women to reduce HIV risk. Trial registration Clinicaltrials.gov, NCT00995176